Cultes et textes sacrés dans l'Égypte tardive Diffusion, circulation et adaptation - Claude, Marion; Abraham Fernández Pichel, Ignacio (Recherches en archéologie, philologie et histoire, 2023)
Far from being isolated units, ancient Egyptian temples were places of numerous points of contact among deities and among men. While these links are well known and tend to show a measure of universality in Egyptian religion throughout the country, each local clergy was intent on modifying this common background to adapt it to the specificity of its own pantheon and sanctuaries. Indeed, it is often difficult to determine with any certainty the precise origin of this or that influence, to postulate the existence of an original source (Urtext), or even to distinguish in each tradition which part proceeds from the "norm" and which is the product of an adaptation. The aim of this book is to contribute to a better understanding of such relationships as well as of the underlying ritual practices in order to highlight the workings of Egyptian religion in the later periods-torn as they are between two apparently contradictory movements: standardization on the one hand and local singularization on the other.